Effects Of HR Management Practices On Employee Innovative Work Behavior With Two Mediation - Marwan Marwan; Fadhliah Alhadar (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This research aims to reveal the influence of human resource management practices on innovative work behaviour and the mediating variables of organisational citizenship behaviour and employee satisfaction. This research was conducted at Khairun University with a sample of 150 people. Data was collected using a questionnaire and distributed via the Google Form application. To analyse the data, Partial Leads Square (PLS) was used. The results of the description of respondents' answers revealed that all research variables were assessed by respondents in the sufficient category. The seven hypotheses tested in this research were declared accepted, both direct and indirect effects. Six have a positive direction of influence, and only one has a negative influence, namely the influence of human resource management practices on innovative work behaviour. So, whether an endogenous variable is good or bad is determined by the condition of the exogenous variable. Based on these findings, it is recommended that severe attention from leadership elements be given to improve all the variables studied to improve the organisation.